Statue of the Goddess of Love in the Populist Discourse of the 1880s - T. V. Dyachuk (Научный диалог, 2019)
The purpose of the research is to conceptualize the role of the statue of the goddess of love in the populist discourse of the 1880s. It is noted that in the era of the crisis of populism, the image of the marble Aphrodite-Venus was claimed as the antithesis of the social and ethical problem of “duty to the people” that had lost its relevance. The article for the first time ever compares the works of G. I. Uspensky and A. I. Ertel. It is shown that the writer Ertel, who declared his break with populism, saw in the ancient statue of Aphrodite the image of all-sufficient beauty, which the artist should return to, getting rid of the mirage of sociality. Unlike Ertel, G. I. Uspensky continued to consider the people as his “creditor” to the end of his life, and the intellectual person as a man obliged to sacrifice himself for the sake of “mass happiness”. For the first time, the influence of N. K. Mikhailovsky on the work of G. I. Uspensky, which was expressed on the scale of artistic synthesis by the author of “Vypryamilo” the evils and ulcers of civilization, is traced. It is indicated that in this case the substratum of populist ideas in “Vypryamilo” was dissolved in Uspensky’s religious-ecstatic revelation about the “bright future” of humanity. It is noted that the statue of Venus de Milo appeared in the essay of Uspensky as a new religious symbol - “prophecy” of the coming Resurrection. The author of the article comes to the conclusion that the crisis of populism was overcome in the essay “Vypryamilo” by a radical move beyond social life, to the “endless prospects” of divine-humanity.